Public Insurance Eligibility and Enrollment for Special Health Care Needs Children - Davidoff, Amy J. (CENTERS for MEDICARE & MEDICAID SERVICES, 2004)
We estimated the proportion of children with special health care needs (CSHCN) eligible for Medicaid and the State Children's Health Insurance Program (SCHIP) using data from the 2000 and 2001 National Health Interview Survey (NHIS) and an algorithm to determine likely eligibility We find that CSHCN were more likely to be eligible compared with other children (50 versus 43 percent), and that they were eligible through different program mechanisms. Relatively few faced waiting periods and premiums to participate in public programs. Participation rates were higher for CSHCN eligible through Medicaid Program rules prior to the SCHIP expansions, compared with those newly eligible after 1997. CSHCN had higher rates of participation than children without special needs (CWOSN), across all eligibility categories.